THE EFFECT OF TABOO GAME ON ENGLISH SPEAKING ABILITY OF ZEN STUDENTS - Pambudi, Raikhan; Faliyanti, Eva; Siagiyanto, Bambang Eko (Premise: Journal of English Education and Applied Linguistics, 2024)
This study aims to determine whether the Taboo game has an effect and significant difference on students’ English speaking ability in the beginner class at Yos Sudarso High School. The research employed a quasi-experimental design, involving a population of 73 students from the beginner class of Yos Sudarso High School academic year 2023/2024. The study conducted in experimental class which consisted of 24 students. The research instrument was an oral test, administered both before and after the treatmenn, to assess students’ speaking ability. Data analysis was conducted using SPSS version 20. The results revealed that the significance level (2-tailed) <0.05, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This confirms that the use of Taboo games in teaching speaking is effective. Additionally, the independent t-test showed a significance level (2-tailed) of 0.000 < 0.05, demonstrating that teaching speaking using the Taboo game has a positive effect on improving students' speaking ability. Therefore, the research concludes that the Taboo game has a significant and positive effect on the speaking abilities of students in the beginner class of Yos Sudarso High School. The findings of this study imply that incorporating interactive activities like the Taboo game can enhance language learning outcomes, suggesting that educators should integrate similar games to improve students' speaking ability.